2017
DOI: 10.1080/13557858.2017.1414157
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in health and health behaviors among gay, lesbian, bisexual and heterosexual men and women in the BRFSS-SOP

Abstract: These findings highlight the need for policy efforts aimed at improving health and health behaviors among lesbian and bisexual women across groups, and more targeted efforts among sexual minority men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…Also, Black and Latinx men reported lower collective self-efficacy at followup. These findings align with previous studies that demonstrate poor health outcomes among sexual minority people of color (Gamarel et al, 2012;Tuthill et al, 2020). Our study provides a better understanding of the association of race/ethnicity and psychosocial resources among sexual minority individuals, that is, through SES.…”
Section: Discussionsupporting
confidence: 91%
“…Also, Black and Latinx men reported lower collective self-efficacy at followup. These findings align with previous studies that demonstrate poor health outcomes among sexual minority people of color (Gamarel et al, 2012;Tuthill et al, 2020). Our study provides a better understanding of the association of race/ethnicity and psychosocial resources among sexual minority individuals, that is, through SES.…”
Section: Discussionsupporting
confidence: 91%
“…Our ndings showed that bisexual men reported a higher rate of cigarette smoking compared to gay men (39.9% vs. 27.3%) in China. This is consistent with literatures in the West that bisexual men often report higher use of cigarette relative to gay men [81,82].…”
Section: Discussionsupporting
confidence: 92%
“…Our ndings showed that bisexual men reported a higher rate of cigarette smoking compared to gay men (39.9% vs. 27.3%) in China. This is consistent with literature in other countries that bisexual men often report higher use of cigarette relative to gay men [77,78].…”
Section: Discussionsupporting
confidence: 92%